OTHR-34. Identifying mechanisms of microglia-tumor cell interactions in retinoblastoma. (3rd June 2022) - Pohlmann, Anike; Gerling, Teresa; Walter, Carolin; Melcher, Viktoria; de Faria, Flavia W; Disch, Alina; Kanber, Deniz; Wöstefeld, Julia; Steenpass, Laura; Lohmann, Dietmar; Ryl, Tatsiana; Riedel, Nicole; et al.
Abstract: BACKGROUND: Treatment-related long-term sequelae and chemotherapy resistance diminish the success of retinoblastoma (RB) treatment. To unravel the mechanisms leading to tumor progression and resistance we examined the intratumoral cellular heterogeneity of RB and its interactions with cells of the tumor microenvironment (TME). METHODS : We used single-cell RNA (scRNA-seq) and ATAC sequencing (scATAC-seq) as well as spatial transcriptomics to analyze and compare RB samples from patients with or without previous chemotherapy (chemo-treated vs. naïve). In addition, we developed a 3D model by injection of RB and TME cells into retinal organoids, which mimics the heterogeneous surrounding of the tumor in a spatially and functionally organized manner. RESULTS : ScRNA-seq revealed a high intratumoral heterogeneity of tumor cells representing distinct developmental stages from progenitors to more differentiated photoreceptor cells. The predominant cell type in the TME was M2-activated microglia (MG). M2-MG exerted multiple receptor-ligand interactions with RB tumor cells which were not found in non-diseased retinas. These tumor-specific cellular interactions regulate multiple signaling pathways (e. g. VEGF-, WNT-, BMP-, PGF- signaling) known to be involved in RB progression. By comparing chemo-treated and chemo-naïve RB samples we were able to identify treatment-resistant and -sensitive subpopulations of tumor cells. Finally, data from our RB-retina in vitro model highlighted the impact of RB cells on gene expression programs of normal retinal cells. CONCLUSION : In summary, we deciphered the intratumoral heterogeneity of RB, uncovered an intricate network of microglia-tumor cell interactions that connects numerous important signaling pathways, and further identified chemotherapy-resistant/sensitive tumor cell populations. The latter observation could prove to be very helpful in the development of novel therapeutic approaches in the treatment of RB.